Hubungan Status Nutrisi terhadap Hiperemesis Gravidarum pada Ibu Hamil di Puskesmas Langsa Lama Kota Langsa Tahun 2023 - Elisa Elisa; Ester Simanullang; Febriana Sari (STIKES Columbia Asia Medan, 2024)
Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women to the point that it interferes with daily work because it generally becomes worse, due to dehydration. The aim of this study was to determine the relationship between nutritional status and hyperemesis gravidarum in pregnant women at the Langsa Lama Health Center, Langsa City in 2023. Case control research design, population of 68 pregnant women. The research results showed a relationship between nutritional status and the incidence of hyperemesis gravidarum in pregnant women at the Langsa Lama Health Center, Langsa City. Pregnant women with poor nutritional status will experience hyperemesis gravidarum 7.5 times compared to pregnant women with good nutritional status. It is recommended that health workers, especially those at Community Health Centers, always inform pregnant women about hyperemesis gravidarum and risk factors for hyperemesis gravidarum. Pregnant women are expected to always seek information about hyperemesis gravidarum and risk factors for hyperemesis gravidarum.